Relationship between ionospheric TEC and geomagnetic SqZ at middle and low latitudes - Niu, Chao; Wei, Yiwei; Xu, Buyun; Li, Xihai; Mu, Xiaodong (Frontiers in Astronomy and Space Sciences, 2022)
Solar quiet variation(Sq) generated from ionospheric currents are among the most important type of geomagnetic variations. In this paper, the correlation between the geomagnetic SqZ component and the ionospheric total electron content (TEC) is discussed. For the analysis, 20 stations at middle and low latitudes are chosen, and the correlation between geomagnetic SqZ and ionospheric TEC at these stations from 2008 to 2015 is analyzed. The time delays are estimated by detecting peaks in the cross-correlation function, which shows that there is a stable correlation between SqZ and TEC. The time delay between them is largest in summer and smallest in winter, which is consistent with the Sq field intensity. With increasing latitude, the time delay decreases gradually from positive to negative, i.e., SqZ goes from being ahead of the TEC to behind it. The turning point of this change is at ca. 28°N, exactly where the Sq current vortex is located.